Magnetotelluric evidence on the southward extension of the Eastern Ghats mobile belt from Ongole, India - CHANDRASEKHAR, E; RAMESH, D; BISWAL, TK (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
There has been a longstanding and scientifically contentious issue, concerning whether or not the Eastern Ghats mobile belt (EGMB) extends southward beyond Ongole in the state of Andhra Pradesh, in south India. Various geological and geophysical investigations carried out in different campaigns could not conclusively address this important issue. Some argued that the EGMB that originates near Mahanadi in the northeast of India and extends along the eastern continental boundary, is abruptly cut near Ongole in the south, swerves eastward towards the Bay of Bengal and joins the erstwhile east Antarctica boundary. Others opined differently and debated about its southward extension beyond Ongole. In the present study, we provide a conclusive evidence for the first time on this perplexing issue, by determining the deep earth electrical resistivity structure of the EGMB region through broad-band magnetotelluric (MT) investigations carried out along two different profiles laid out one near the Ongole region (profile AA' of 35 km length) and the other near the Nellore region (profile BB' of 52 km length). The latter is located at a distance of about 125 km south of the former. The lengths of both these profiles are sufficiently far from the influences of the electrical nature of the subsurface of the adjoining geological terrains namely, the east Dharwar craton, the Cuddappah basin and the southern granulite terrain. This enables to determine the electrical nature of the EGMB alone and examine whether or not it extends south of Ongole. Two-dimensional inversion of MT data of both the profiles revealed a very thin top conductive layer of about 1-10 Omega-m with an average thickness of about 500 m, representing the alluvium. This layer is underlain by very high resistive subsurface with resistivity of about 10(7) Q-m extending up to about 30 km and probably further beyond (not shown in the present study). Since the major rock types in the study area, namely, Khondalites, Calcgranulites, Charnockites and Granitic gneisses of Archaean age, have large overlapping resistivities, MT data could not explicitly discern the nature of the multilayered crust beneath the EGMB. As a result, the subsurface beneath both the regions shows up as a very thick single layer of very high resistivity. The high grade rocks of the Ongole domain and supracrustals of Nellore Schist Belt (NSB), which lies south of Ongole domain, have undergone synchronous tectonic activity at ca.1.6 By. This is evident by the Kanigiri and Kandra ophiolites within NSB that signify the Proterozoic subduction of the EGMB. This geological evidence together with the similar nature of the high electrical resistivity of the subsurface observed at Ongole and Nellore regions confirm the southward extension of the EGMB beyond Ongole.